2011
DOI: 10.1093/humrep/der377
|View full text |Cite
|
Sign up to set email alerts
|

CFTR mutations in men with congenital bilateral absence of the vas deferens (CBAVD): a systemic review and meta-analysis

Abstract: In summary, our results demonstrate a high frequency of CFTR mutations in CBAVD patients, and these exhibit evident ethnic differences. In addition, 5T allele and 5T/(TG)12_13 may contribute to the increased risk for CBAVD, with the 5T penetrance probably being modulated by adjacent (TG)12_13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
124
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 73 publications
5
124
2
Order By: Relevance
“…7 On the other hand, a large number of reports have described the CFTR mutation in infertile patients with CBAVD, but their results were not completely consistent. 22 The main objectives of this study were to determine the possible involvement of CFTR dysfunction in CBAVD males from China, a country with a …”
Section: Discussionmentioning
confidence: 99%
“…7 On the other hand, a large number of reports have described the CFTR mutation in infertile patients with CBAVD, but their results were not completely consistent. 22 The main objectives of this study were to determine the possible involvement of CFTR dysfunction in CBAVD males from China, a country with a …”
Section: Discussionmentioning
confidence: 99%
“…CF affects the function of several organs, in particular the trachea, lung, pancreas and several tissues of the reproductive system (Chan et al, 2009;Guggino and Stanton, 2006;O'Sullivan and Freedman, 2009;Quinton, 1999;Rowe et al, 2005). Almost all male CF patients are diagnosed with congenital bilateral absence of the vas deferens (CBAVD) and concurrent absence or atrophy of a large portion of the epididymis (Anguiano et al, 1992;Cuppens and Cassiman, 2004;Oates and Amos, 1994;Patrizio and Zielenski, 1996;Yu et al, 2012). These organs are located downstream of the testis; they are required for sperm maturation, storage and transport, and are thus essential for the establishment of male fertility (Chen et al, 2012b;Cornwall, 2009;Robaire et al, 2006;Shum et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reproductive tract can also be negatively impacted, resulting in infertility. Ninety-seven percent of men affected with CF have congenital bilateral absence of the vas deferens (CBAVD), and women with CF are often infertile owing to thickened cervical mucus, disruption of the uterine environment, delayed puberty, and ovulatory dysfunction (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…In addition, male CF carriers have been shown to be at higher risk for fertility issues. Twenty-five percent of men with CBAVD only have one CFTR mutation, and there is an increased CFTR mutation frequency in groups of men with non-CBAVD infertility such as those with nonobstructive azoospermia, oligospermia, and asthenospermia (16,17,32,33). Most recently, a study by Lu et al in 2014 demonstrated an increase in the frequency of miscarriages/still births and prevalence of CBAVD in male CF carriers (34).…”
mentioning
confidence: 99%